Pseudepigraphic perspectives : the Apocrypha and Pseudepigrapha in light of the Dead Sea scrolls : proceedings of the International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 12-14 January, 1997 - Chazon, Esther G.; Stone, Michael E., 1938-; Pinnick, Avital. (Studies on the Texts of the Desert of Judah, 1999)
This volume of symposium papers examines the attribution of books to great figures in antiquity: Enoch, Noah, Abraham, Levi, Moses, Ezekiel, Daniel and others. The authors offer fine literary studies of these pseudepigraphical writings, assess the uses of pseudonymity and anonymity in the Dead Sea Scrolls and rabbinic literature, and explore the theological, social and historical implications of the different attributions and approaches. The consequences of assigning the origins of evil to humans (Adam and Eve) or to demons (the generations of Enoch and Noah) and the significance of each author's choice of pseudepigrahical pseudonym for identifying his social context are among the important issues addressed.